To Cover or to Hide? The Role of the Media in the Trials of the Nazis and Their Collaborators - Tomas Vaiseta (Lietuvos Istorijos Studijos)
Rec.: Ruth Leiserowitz, Gintarė Malinauskaitė, Hektoras Vitkus (eds.), Making Justice Visible: War Crimes Trials, Media and Memory after World War II, Osnabrück: fibre Verlag, 2022.